Implementasi Logika Fuzzy Tsukamoto Dalam Web Prediksi Banjir Di Kabupaten Blitar - Umi Hanik; Virganda Rimba Asmara; Rizky Yunis Teresya; Zoulvia Hanest Khinanti; Asshyffatul Aina Ni’mah; Bintang Lailatul Mukaromah (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2025)
Flooding is one of the natural disasters that frequently occurs in Indonesia, causing material losses and loss of life. To support early warning systems and risk mitigation, accurate flood prediction is needed. This study focuses on applying the Tsukamoto fuzzy logic method to predict flood potential in the Blitar Regency. The choice of this method is based on its ability to handle data uncertainty and produce more accurate predictions through the rule-based defuzzification process. The main variables analyzed include rainfall, river discharge, and regional characteristics that influence the likelihood of flooding. The results of the study show that the Tsukamoto fuzzy logic method can predict flood potential with a high level of accuracy, which is in line with findings from previous studies. It is hoped that this fuzzy logic-based prediction system can provide an effective solution for early warning, reduce the impact of flooding, and support decision-making in flood disaster mitigation in the Blitar Regency.